PENGARUH FAKTOR PSIKOLOGIS TERHADAP PENCAPAIAN (ACHIEVEMENT) HAFALAN MAHASISWI FAKULTAS TARBIYAH IIQ JAKARTA - Fauziah, Azza Nabila; Khusnia, Alfun (Jurnal Qiroah, 2019)
This research is a type of quantitative research conducted at the Al-Qur'an Institute of Sciences (IIQ) Jakarta, starting from February to July 2019. The population in this study are all female students of the Tarbiyah Faculty of the Qur'an Sciences Institute (IIQ) Jakarta, with a sample of 35 female students using random sampling techniques.Data collection using a questionnaire. Instrument analysis technique uses validity test and reliability test. Test the hypothesis using the product moment. The data obtained are primary data which are the results of respondents' answers to the questionnaire distributed. The results showed that there was a significant influence between the influence of psychological factors on the achievement of memorization of Tarbiyah IIQ Jakarta faculty students. It can also be seen that the magnitude of the psychological influence on the achievement of the memorization of Tarbiyah IIQ Jakarta faculty students is 5,56%. While the rest is influenced by other factors not examined in this study.